Britain in the first age of party, 1680-1750 : essays presented to Geoffrey Holmes - Holmes, Geoffrey S., 1928-; Jones, Clyve, 1944- (Hambledon Press, 1987)
The 70 years of late Stuart and early Hanoverian Britain following 1680 were a crucial period in British politics and society, seeing the growth both of political parties and of stability. This collection of original essays provides a coherent account of Britain in the ''First Age of Party''.